Waiting Time Experiences and Perceptions Among National Health Insurance Patients in Outpatient Care - Muhammad Alamsyah; Yuanita Windusari; Haerawati idris (Journal La Medihealtico, 2025)
Waiting time is a critical aspect of healthcare service quality that influences patient satisfaction and overall service evaluation. This study aims to explore patients’ perceptions of waiting time in healthcare services by examining experiential factors that shape how waiting is interpreted and tolerated. A qualitative research design was employed, using in-depth interviews with four patients who had direct experience with healthcare service delivery. Data were analyzed thematically to identify recurring patterns in participants’ accounts. The findings reveal that perceptions of waiting time were influenced not only by its duration but also by procedural clarity, staff responsiveness, communication and information transparency, service environment, and the presence of personalization and emotional support. Clear service procedures and timely, understandable information reduced uncertainty and moderated negative perceptions of waiting. Additionally, clean and comfortable environments, along with empathetic and attentive staff interactions, enhanced patients’ ability to tolerate waiting and contributed to more positive service experiences. The study concludes that waiting time should be understood as a multidimensional experience shaped by both operational and interpersonal factors. These findings highlight the importance of adopting patient-centered strategies that integrate effective communication, environmental comfort, and emotional support in managing waiting time within healthcare services.